Digital Literacy Skills and Utilization of Online Platforms for Teaching by LIS Educators in Universities in Rivers State, Nigeria - David-West, Boma Torukwein (International Journal of Knowledge Content Development & Technology, 2022)
The study investigated digital literacy skills and utilization of online platforms for teaching by LIS educators in universities in Rivers State, Nigeria. The study was undertaken as a descriptive survey design. Three research questions and three hypotheses guided this study. The population of the study was twenty-six Lecturers from the three universities in Rivers State where library and information science are offered. The twenty-six constitute the sample size. Census sampling technique was adopted for the study. The instrument titled Digital Literacy Skills and Utilization of Online Platform for Teaching Questionnaire (DLSOPUQ) was used to elicit information from the respondents. Twenty-six copies of the questionnaire were administered and retrieved. Mean (x̅) was used to analyze the research questions and the null hypotheses was tested with t-test at 0.05 level of significance. The study revealed that there is no significant difference between digital literacy and utilization of online platforms for teaching by LIS educators in universities in Rivers State. Further findings revealed that LIS educators do not have the necessary skills to navigate the online environment for teaching without assistance. In conclusion LIS educators should be innovative and update their skills to meet up with global practice. It was recommended among others that LIS educators should be trained and retrained by the university management to cope with online teaching and provision of the right infrastructure by governments for effectives teaching and learning process.